A Multidimensional Cross-Sectional Analysis of Coronavirus Disease 2019 Seroprevalence Among a Police Officer Cohort: The PoliCOV-19 Study. (16th October 2021) - Sendi, Parham; Baldan, Rossella; Thierstein, Marc; Widmer, Nadja; Gowland, Peter; Gahl, Brigitta; Büchi, Annina Elisabeth; Güntensperger, Dominik; Wider, Manon; Blum, Manuel Raphael; Tinguely, Caroline; Maillat, Cédric; et al.
Abstract: Background: Protests and police fieldwork provide a high-exposure environment for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. In this cross-sectional analysis, we investigated the seroprevalence among a police cohort, and sociodemographic, work, and health-related factors associated with seropositivity. Methods: Study participants were invited for serological testing of SARS-CoV-2 and to complete online questionnaires. Serum neutralization titers toward the wild-type SARS-CoV-2 spike protein (expressing D614G) and the Alpha and Beta variants were measured in seropositive study participants. Results: A total of 978 police personnel representing 35% of the entire staff participated from February to March 2021. The seroprevalence was 12.9%. It varied by geographic region, ranged from 9% to 13.5% in 3 regions, including the city; and was 22% in Bernese Seeland/Jura with higher odds for seropositivity (odds ratio [OR], 2.38 [95% confidence interval CI, 1.28–4.44], P =.006). Job roles with mainly office activity were associated with a lower risk of seropositivity (OR, 0.33 [95% CI, .14–.77], P =.010). Self-reported compliance with mask wearing during working hours was 100%; 45% of seropositive vs 5% of seronegative participants ( P <.001) reported having had contact with a proven coronavirus disease 2019 (COVID-19) case living in the same household prior to serological testing. The level of serum antibody titers correlated with neutralization capacity. Antibodies derived from natural SARS-CoV-2 infection effectively neutralized the SARS-CoV-2 spike protein, but were less effective against the Alpha and Beta variants. Conclusions: The seroprevalence of anti–SARS-CoV-2 antibodies of police officers was comparable to that reported in the general population, suggesting that the personal protective equipment of the police is effective, and that household contacts are the leading transmission venues. The level of serum antibody titers, in particular that of anti-spike antibodies, correlated well with neutralization capacity. Low antibody titers acquired from natural infection were not effective against variants. Clinical Trials Registration: NCT04643444. Abstract : The seroprevalence of anti–SARS-CoV-2 antibodies of police officers was comparable to that reported in the general population. The level of serum antibody titers correlates well with neutralization capacity. Low antibody titers acquired from natural infection are not effective against variants.